Analysis of athletes performing high-demand tests: Linking employment status with motivation, identity, and dependency - Ordóñez Ontiveros, Yanko; León Quismondo, Jairo; Burillo Naranjo, Pablo (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to analyze a new aspect of sport by studying those athletes of legal age and non-professionals who decide to take the step to participate in highly demanding sports events. Through a survey based on three validated scales (MOMS, AIMS and EDS), data on motivation, identity and dependence on exercise were collected from 387 athletes (320 men and 67 women) whose age range was between 18 and 74 years. In addition to psychosocial factors, sociodemographic aspects such as educational level and employment status were analyzed, resulting in 17 studied variables whose mean values of internal consistency presented a remarkable degree of reliability. Among other results, it can be highlighted that gender significantly (p<0.05) affects the subscales of weight, recognition and social identity in favor of men, while in meaning of life and self-esteem it does so in favor of women (p<0.05) and that the variables that are most frequently associated with others are desired effects, lack of control, and reduction of other activities. The study can help sports managers plan the design of these tests based on the type of user they are targeting.